2005
DOI: 10.1007/s10310-005-0148-9
|View full text |Cite
|
Sign up to set email alerts
|

Histological studies of shoot regeneration system in hypocotyl-derived callus of Phellodendron amurense Rupr.

Abstract: An efficient in vitro plant regeneration was achieved from hypocotyl-derived callus of a medicinal tree Phellodendron amurense. The expected morphogenic response was obtained on the media containing 0.89 mM 6-benzyl aminopurine (BAP) plus 4.52 mM 2.4-dichlorophenoxyacetic acid (2,4-D), 4.44 mM BAP plus 5.37 mM a-naphthaleneacetic acid (NAA), or 2.22 mM BAP plus 4.92 mM indole-3-butyric acid (IBA). A detailed histological study was undertaken to gain a better understanding of cellular changes that take place du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Therefore, we could say that 2,4-D produces SEs but blocks root induction. Azad et al (2005c) reported the similar observation in P. amurense.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, we could say that 2,4-D produces SEs but blocks root induction. Azad et al (2005c) reported the similar observation in P. amurense.…”
Section: Resultssupporting
confidence: 78%
“…(e) Germination of SE without rooting showing shoot apex (SA), leaf primordium (LP), and PC, which were developed in MS medium containing 8.8 μM BA plus 4.0 μM 2,4-D. f Germination of SE showing SA, LP, PC, and RP which were developed in MS medium containing 8.8 μM BA plus 4.0 μM NAA. NB: (e) cited byAzad et al (2005c).…”
mentioning
confidence: 99%
“…In our present investigation type II callus showed greenish yellow nodular structure as in case of Curculigo orchioides [23]. Different developmental stages of somatic embryo like globular, leaf primordials were evident from histological studies of leaf derived calli as in case of Phellodendron amurense [24] Alginate is one of the common polymer used for production of synthetic seeds. It exhibits greater variation in viscosity, resulting in difficulty for decanting and encapsulation.…”
Section: Discussionmentioning
confidence: 99%
“…Terms & Conditions of access and use can be found at http:// www.tandfonline.com/page/terms-and-conditions Introduction Phellodendron amurense Rupr. (Rutaceae) is a deciduous tree commonly called the Amur cork tree (Azad, Yokota, Ishiguri, et al 2005;Wang et al 2009). Indigenous to the Amur Valley at the boundary between Northeastern China and the Russian Far East (Lis et al 2004), P. amurense is now distributed in Northeastern China, Inner Mongolia, the Russian Far East, and southern Sakhalin, Korea, and Japan (Yang et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%